CULTURAL MORPHOLOGICAL AND BIOCHEMICAL CHARACTERISTICS OF BACILLUS SUBTILIS STRAINS - V. S. Rusaleyev; О. V. Pruntova; D. A. Vasilyev (Ветеринария сегодня)
A decrease in therapeutic eﬀect of some live lacto- and bifdobacteria-based drugs for veterinary use has been observed for the last 20 years that urges scientists to search for new microorganisms possessing probiotic properties. Many studies in this feld are focused on Bacillus subtilis that is widespread in the environment and non-pathogenic for animals and humans. Results of tests of Bacillus subtilis for its biological properties and antagonistic activity aimed at optimization of methodical approaches for detection of strain with the highest antagonistic eﬀect on some opportunistic microorganisms and their further use as probiotics are described. Cultural morphological and biochemical characteristics of the tested strains conformed to the species characteristics of Bacillus subtilis. Tested strains were nonpathogenic for white mice. Tests showed that spore biomass could be prepared both in liquid and on solid nutrient media. Methodically, spore biomass preparation in liquid nutrient medium is preferable. The tests showed that spores emerged from anabiosis non-uniformly and it depended on original seed spore storage period. Spore cultures stored less than one year emerged from anabiosis more quickly. It was found that the spores formed more readily when the cultures were aerated with oxygen as well as that lag-phase culture medium had a stimulating eﬀect on Bacillus subtilis spore germination. Bacillus subtilis strains were found to have antagonistic eﬀect on Escherichia coli, Salmonella and Staphylococcus. Area of growth inhibition of the said bacteria was 15–20 mm. Tested Bacillus subtilis strains could be proposed for use as probiotics.